Nano drug delivery platform based on thermosensitive PEG-PCL hydrogel encapsulated in silver-bearing micelles and its antifungal activity investigation against vaginal candidiasis - Hosseinzadeh, Fatemeh; Tabesh, Hadi; Farzaneh, Farah (Frontiers in Materials, 2023)
Vaginal candidiasis is a genital mucosal disease. Polymeric micelles (PMs) utilization due to improved solubility and low bioavailability of hydrophobic drugs e.g. clotrimazole is of interest. Silver nanoparticles could be applied to enhance antifungal properties. Loading PMs in injectable thermosensitive hydrogels by rapid distribution across vaginal walls improves the bioavailability of the drug and provides suitable therapeutic efficiency for drug delivery systems. PCL-PEG-PCL (LGL) and PEG-PCL-PEG (GLG) copolymers were characterized by FTIR, HNMR, and GPC. Zeta potential and Size of synthesized PMs were determined by EMSA and DLS technics and morphological examination of PMs was conducted by FESEM and TEM. Silver-bearing polymeric micelles (PM-Ag) were characterized by DLS and LDE technics. EDX and UV-VIS spectroscopy confirmed silver nanoparticles' binding to PMs. Thermosensitive GLG hydrogel was considered a carrier for PM-Ag. Encapsulation efficiency and drug loading content of micelles were calculated 64.53% and 14.6% respectively. The diameter and zeta potential of PMs were measured 166 ± 1.73 nm±SD and -6.26 ± 0.3 mV±SD and after silver-bearing it reached 197 ± 2.29 nm±SD and -5.38 ± 0.45 mV±SD respectively. The biocompatibility of samples was investigated by MTT assay and the results indicated that up to a concentration of 125 µg/mL, the relative cell viability percentage exceeded 80%. Therefore, by considering the acceptable antifungal activity of the samples against C. Albicans, the designed drug delivery system is capable of sustained drug release over a specified period.